Subcutaneous abscess caused by Trueperella pyogenes in a Southern pudu (Pudu puda) - Llanos-Soto,Sebastián (Universidad Austral de Chile. Facultad de Ciencias Veterinarias, 2020)
ABSTRACT: A case of an abscess on the head of a captive Southern pudu (Pudu puda) caused by Trueperella pyogenes is described. A diagnosis was done based on bacterial culture and MALDI-TOF MS identification. Traumatic inoculation of the bacterium in the subcutaneous tissue is speculated.